FasterSparql: an architecture for query mediation over loosely coupled federations of knowledge graphs - Huf, Alexis Armin (2025)
Tese (doutorado) - Universidade Federal de Santa Catarina, Centro Tecnológico, Programa de Pós-Graduação em Ciência da Computação, Florianópolis, 2025.